Physical model for the exotic ultraviolet photo-conductivity of ZnO nanowire films - 潘跃武 任守田 曲士良 王强 (Chinese physics B, 2013)
Employing a simple and efficient method of electro-chemical anodization, ZnO nanowire films are fabricated on Zn foil, and an ultraviolet （UV） sensor prototype is formed for investigating the electronic transport through back-to-back double junctions. The UV （365 nm） responses of surface-contacted ZnO film are provided by I-V measurement, along with the current evolution process by on/off of UV illumination. In this paper, the back-to-back metal-seconductor-metal （M-S-M） model is used to explain the electronic transport of a ZnO nanowire film based structure. A thermionic-field electron emission mechanism is employed to fit and explain the as-observed UV sensitive electronic transport properties of ZnO film with surface-modulation by oxygen and water molecular coverage.